EXPLORING THE LIVED EXPERIENCES OF PATIENTS AFTER CORONARY ARTERY BYPASS GRAFTING: A SCOPING REVIEW OF QUALITATIVE EVIDENCE - Rofidin, Opi; Ibrahim, Kusman; Kurniawan, Titis (International Archives of Medical Sciences and Public Health, 2026)
Coronary Artery Bypass Grafting (CABG) is an effective revascularization procedure; however, postoperative recovery extends beyond clinical outcomes and involves complex physical, psychological, social, and spiritual dimensions. Understanding patients’ lived experiences is essential to develop holistic and patient-centered care. This study aimed to synthesize qualitative evidence on the lived experiences of patients following CABG. A scoping review was conducted following the Arksey and O’Malley framework and reported in accordance with PRISMA-ScR guidelines. A systematic search was performed across PubMed, Scopus, Taylor & Francis, and EBSCO databases. Studies were selected using predefined inclusion and exclusion criteria based on the PCC (Population, Concept, Context) framework. A total of 14 qualitative studies published between 2015 and 2026, conducted across 10 countries, were included. Data were analysed using a descriptive and thematic synthesis approach, categorizing extracted data to identify recurring patterns, then synthesizing findings across physical, psychological, social, and spiritual dimensions of recovery. The synthesis identified four overarching themes: (1) psychospiritual transformation and meaning reconstruction, (2) gaps in information, communication, and patient involvement, (3) physical burden and functional limitations, and (4) social role disruption and structural barriers to recovery. The synthesis results show that post-CABG patient recovery is influenced by various aspects, including psychospiritual changes, physical limitations, lack of information and patient involvement, and social barriers in carrying out daily roles. Therefore, a more comprehensive treatment approach is needed to optimally support the patient’s recovery process.